Additive Manufacturing: Advances in Trends and Technology (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The latest process involved in the design, development and delivery of products to the end users has been implemented utilizing additive manufacturing (AM) or three-dimensional (3D) printing. This technology provides a great deal of freedom in the production of complicated parts, highly personalized goods and effective waste reduction. The new technological and Industrial revolution, utilizes the incorporation of intelligent fabrication and CAD processes. Via its various advantages, such as time and material savings, rapid prototyping, has enhanced productivity as well as distributed manufacturing processes, where AM actively participates and plays significant role in the industrial advancements. This paper is intended to conduct an analytical review of the latest developments and technological aspects in the AM innovation. This paper also explores the viability of the additive manufacturing mechanism as well as the advantages of the product in global, social and ecological fields. At last, the paper finishes with an outline of AM's potential in technologies, implementations and products developments, which will generate new concepts for AM discovery in the coming years..